Respuesta :

2sec²(x) - 2sec²(x)sin(x) - sin²(x) - cos²(x) = 1
2sec²(x) - 2sec²(x)sin(x) - sin²(x) - cos²(x) = sin²(x) + cos²(x)
                                     + sin²(x) + cos²(x) + sin²(x) + cos²(x)
                           2sec²(x) - 2sec²(x)sin(x) = 2sin²(x) + 2cos²(x)
                       2[sec²(x)] - 2[sec²(x)sin(x)] = 2[sin²(x) + cos²(x)]
                           2[sec²(x) - sec²(x)sin(x)] = 2(1)
                                                2                     2
                               sec²(x) - sec²(x)sin(x) = 1
                                             sec²(x)         sec²(x)
                                                   1 - sin(x) = cos²(x)
                            sin²(x) + cos²(x) - sin(x) = cos²(x)
                                        - cos²(x)              - cos²(x)
                                           sin²(x) - sin(x) = 0
                             sin(x)[sin(x)] - sin(x)[1] = 0
                                        sin(x)[sin(x) - 1] = 0
                    sin(x) = 0      or      sin(x) - 1 = 0
           sin⁻¹[sin(x)] = sin⁻¹(0)                + 1 + 1
                          x = 0                      sin(x) = 1
                                                sin⁻¹[sin(x)] = sin⁻¹(1)
                                                               x ≈ 1.5707

The solution is actually equal to zero.
ACCESS MORE